Growth and scintillation properties of Tl-doped CsI/CsCl/NaCl ternary eutectic scintillators. (10th December 2020) - Takizawa, Yui; Kamada, Kei; Yoshino, Masao; Yamaji, Akihiro; Kurosawa, Shunsuke; Yokota, Yuui; Sato, Hiroki; Toyoda, Satoshi; Ohashi, Yuji; Hanada, Takashi; Kochurikhin, Vladimir. V.; Yoshikawa, Akira
Abstract: Tl:CsI/CsCl/NaCl eutectic scintillators were grown by the Bridgman–Stockbarger method. The eutectic phases were uniformly distributed in the transverse direction and slightly aligned along the growth direction. Then, the CsI phase can be designed as columnar. The expected emission peak observed at 550 nm was observed under X-ray excitation and cathodoluminescence and was ascribed to the self-trapped exciton perturbed by TI + in Tl:CsI. The mapping of optically waveguided light emission was observed by confocal laser microscopy, consequently optical waveguiding of Tl + emission in the CsI phase was demonstrated.